Masjid Agung Tuban : Studi Tentang Fungsi Dalam Kehidupan Sosial Kemasyarakatan 2004-2020: Great Mosque of Tuban: Study of Functions in Social Life 2004-2020 - Windari, Sri; Nafita Amelia Nur, Hanifah (Journal of Islamic History, 2021)
This paper examines the function of the Great Mosque of Tuban in Social Life, which is limited from 2004-2020. This research is a follow-up study that uses the structural-functional theory proposed by Talcott Parsons. This research is descriptive analysis using historical research methods related to data collection, verification, interpretation, and historiography. This study aims to determine the history of the Great Mosque of Tuban and analyze its function in social life. From a historical point of view, the Great Mosque of Tuban has existed since the time of Wali Songo, namely Sunan Bonang who is a prominent Islamic broadcaster in Tuban. Along with the times, in principle the Great Mosque of Tuban is not only used as a place of worship, but also functions as a social activity such as a place for distributing zakat and infaq, wedding activities, recitations, and as an economic center. In addition, it is also used as a tourist attraction.